Reputation and Mechanism Choice in Procurement Auctions – An Experiment - Jeannette Brosig; Timo Heinrich (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
We experimentally study the role of reputation in procurement using two common mechanisms: price-based and buyer-determined auctions. While buyers are bound to buy from the lowest bidder in price-based auctions, they can choose between bidders in buyer-determined auctions. Only in the latter buyers can consider the reputation of bidders. We find that bidders supply higher quality in buyer-determined auctions leading to higher market efficiencies in these auctions. Accordingly, buyers prefer the buyer-determined auction over the price-based auction, while only half of the bidders do so. A more detailed analysis of buyers' and bidders' behavior and profits provides insights into their mechanism choice. – – In dieser experimentellen Studie untersuchen wir die Rolle von Reputation in der Beschaffung mit Hilfe von zwei verbreiteten Mechanismen: preisbasierten und käuferbestimmten Auktionen. Während die Käufer in preisbasierten Auktionen vom Niedrigstbietenden kaufen, können sie in käuferbestimmten Auktionen frei zwischen den Bietern wählen. Nur in käuferbestimmten Auktionen können Käufer die Reputation der Bieter berücksichtigen. Unsere Ergebnisse zeigen, dass Bieter in käuferbestimmten Auktionen eine höhere Qualität anbieten. Dies führt zu einer höheren Markteffizienz in diesem Auktionsmechanismus. Dementsprechend bevorzugen Käufer die käuferbestimmte Auktion gegenüber der preisbasierten während nur die Hälfte der Bieter diese Präferenz offenbart. Eine detaillierte Analyse des Verhaltens und der Gewinne von Käufern und Bietern gibt Einblicke in ihre Wahl des Auktionsmechanismus.
Keywords: D44; C91; C72; 330; Buyer-determined and price-based procurement; reputation information; auction choice; experimental economics; Beschaffung; Auktionstheorie; Marktmechanismus; Reputation; Test